POLEMIK HUKUM PEMERINTAHAN DESA (Studi di Desa Handapherang Kecamatan Cijeungjing Kabupaten Ciamis): Array - H. Zulkarnaen; Tintin Marliah; Budi Setiaman; Yussana Yussana (Program Studi Hukum Program Pasca Sarjana, 2020)
The village administration in each regency has different authorities but must refer to the current law. So in this study only focused on polemic changes in the law on the Village which is applied by one of the Village Governments in Ciamis Regency which will affect the change in authority of the Village Head. This research uses normative legal methods using secondary data types. The data collection technique used is library research. After the data collection and processing stage, the next stage is analyzing the data. Appointment of village apparatus that does not have a KTP in a nominating village or does not live or is domiciled in the village is abolished by the decision of the Constitutional Court No. 128 / PUU / XIII / 2015 concerning the abolition of the conditions of domicile for prospective village officials through the review of Article 33 letter g and Article 50 paragraph (1) letter (c) of Law No. 6 of 2014 concerning Villages In addition, the task of village officials who are 60 years old can still carry out their duties before the Village Law and implementing regulations are determined. This is in accordance with the circular letter of the Directorate General of Community Empowerment and Village Ministry of Home Affairs Number 140/2035 / PMD dated March 26, 2015 which states that village officials who are not Civil Servants (PNS) status continue to carry out their duties until the end of their tenure.